Candida albicans mycotic aneurysm of aortic arch following laparoscopic right hemicolectomy for colon cancer. Issue 6 (24th June 2021) - Rushforth, Eve; Hamed, Mazin; Aryal, Kamal
Abstract : An 81-year-old man was referred to the colorectal surgeons for an elective laparoscopic right hemicolectomy for a caecal adenocarcinoma (T2N0M0). The operation was uneventful; however, 12 days postoperatively the patient developed symptoms of sepsis of unknown origin. After extensive investigations and work up, Candida albicans was grown as the causative organism with the site of infection being a new saccular mycotic aneurysm arising from the distal, posterior aspect of the aortic arch. The mycotic aneurysm was not initially considered as a differential diagnosis, and this case highlights the importance of consideration of mycotic aneurysm as a differential diagnosis in postsurgical septic patients.